Histological Changes in Skeletal Muscle During Death by Drowning: An Experimental Study. (June 2016) - Girela-López, Eloy; Ruz-Caracuel, Ignacio; Beltrán, Cristina; Jimena, Ignacio; Leiva-Cepas, Fernando; Jiménez-Reina, Luis; Peña, José
Abstract : Abstract: A diagnosis of drowning is a challenge in legal medicine as there is generally a lack of pathognomonic findings indicative of drowning. This article investigates whether the skeletal muscle undergoes structural changes during death by drowning. Eighteen Wistar rats were divided into 3 equal groups according to the cause of death: drowning, exsanguination, and cervical dislocation. Immediately after death, samples of the masseter, sternohyoid, diaphragm, anterior tibial, soleus, and extensor digitorum longus muscles were obtained and examined by light and electron microscopy. In the drowning group, all muscles except the masseter displayed scattered evidence of fiber degeneration, and modified Gomori trichrome staining revealed structural changes in the form of abnormal clumps of red material and ragged red fibers. Under the electron microscope, there was myofibrillar disruption and large masses of abnormal mitochondria. In the exsanguination group, modified Gomori trichrome staining disclosed structural changes and mitochondrial abnormalities were apparent under light microscopy; however, there was no evidence of degeneration. No alterations were observed in the cervical dislocation group. As far as we know, this is the first time that these histological findings are described in death by drowning and are consistent with rhabdomyolysis and intense anoxia of skeletal muscle.